Bridging the nano-scale interphase with macro-scale properties: Two-step simulating of electrical conductivity for polymer composites incorporating carbon nanofibers - Yasser Zare; Muhammad Tajammal Munir; Kyong Yop Rhee; Soo-Jin Park (Journal of Materials Research and Technology, 2025)
The theoretical attitudes for conductivity of polymer-carbon nanofiber (CNF) system entitled as PCNFs are imperfect, thus constraining the upgrading of high-quality products. To address this limitation, a novel two-phase methodology is developed to approximate the PCNF conductivity, taking into account the interphase/CNF network and the tunnel zone among proximate CNFs. In Step I, the CNF/interphase is conceptualized as pseudoparticles, and their conductivity is determined using a simplified equation. In Step II, the tunneling distance among the pseudoparticles is considered, and the overall conductivity of the PCNFs is subsequently predicted. This two-step methodology is verified against experiential conductivity data for various examples. In addition, the inspiration of multiple features on the PCNF conductivity is thoroughly analyzed to substantiate the methodology. The results demonstrate a satisfactory association between the experimented and estimated conductivity of the composites. Notably, minimal CNF content (1 vol%), maximal waviness, the thickest and shortest nanofibers, the narrowest interphase, and the largest tunneling space fail to enhance the conductivity of system. In contrast, minimizing the tunneling distance to 2 nm and the percolating onset to 0.006 markedly improve the nanocomposite conductivity to 0.45 S/m.